How Well Can Modern Nonhabitual Barefoot Youth Adapt to Barefoot and Minimalist Barefoot Technology Shoe Walking, in regard to Gait Symmetry. (29th October 2017) - Xu, Y.; Hou, Q.; Wang, C.; Simpson, T.; Bennett, B.; Russell, S.
Abstract : We aim to test how well modern nonhabitual barefoot people can adapt to barefoot and Minimalist Bare Foot Technology (MBFT) shoes, in regard to gait symmetry. 28 healthy university students (22 females/6 males) were recruited to walk on a 10-meter walkway randomly on barefoot, in MBFT shoes, and in neutral running shoes at their comfortable walking speed. Kinetic and kinematic data were collected using an 8-camera motion capture system. Data of joint angles, joint forces, and joint moments were extracted to compute a consecutive symmetry index. Compared to walking in neutral running shoes, walking barefoot led to worse symmetry of the following: ankle joint force in sagittal plane, knee joint moment in transverse plane, and ankle joint moment in frontal plane, while improving the symmetry of joint angle in sagittal plane at ankle joints and global (hip-knee-ankle) level. Walking in MBFT shoes had intermediate gait symmetry performance as compared to walking barefoot/walking in neutral running shoes. We conclude that modern nonhabitual barefoot adults will lose some gait symmetry in joint force/moment if they switch to barefoot walking without fitting in; MBFT shoe might be an ideal compromise for healthy youth as regards gait symmetry in walking.